2005
DOI: 10.1159/000084182
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Human Expressed Sequences Newly Identified in Silico as Tumor Specific

Abstract: In our previous studies, we used global computational differential display of ESTs that belong to UNIGENE clusters and identified human sequences differentially expressed in human tumors, as well as a considerable amount of transcripts represented only in tumor-derived cDNA libraries. Most of the tumor-specific EST clusters are derived from the plurality of the tumor types originated in tissues of both ectodermal and mesodermal origin. We found that many of such tumor-specific ESTs do not contain long open rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
20
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 9 publications
6
20
0
1
Order By: Relevance
“…Experimental data confirmed the results obtained in silico , i.e., the tumor-specificity of expression of these sequences [4]. …”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…Experimental data confirmed the results obtained in silico , i.e., the tumor-specificity of expression of these sequences [4]. …”
Section: Introductionsupporting
confidence: 80%
“…133294 includes an alternatively spliced isoform of the IQGAP3 gene that arises by retention of its 672-nt intron. Earlier [4], we demonstrated that this isoform is characterized by broad tumor-related and embryonal expression, thus representing a new carcinoembryonic transcript.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…In the present work, we have used a computer-based differential display (CDD) analysis tool, designated HSAnalyst, to conduct global comparison of expressed sequence tag (EST) clusters belonging to the human Unigene database (6,7). Among a list of various genes highly represented in tumorderived libraries and rarely observed in normal tissue-derived libraries was the Unigene cluster Hs.389457, which contains the complete mRNA sequence of human Brachyury, a homologue of the mouse Brachyury gene (8).…”
mentioning
confidence: 99%